Empowering a Village Community Through Training on Healthy Lifestyle and Appropriate Medicine-Related Behaviour - Sylvi Irawati; Aguslina Kirtishanti; Vendra Setiawan; Astridani Risky Putranti; Reine Risa Risthanti; Finna Setiawan; Nikmatul Ikhrom Ekajayani (Nusantara Science and Technology Proceedings, 2024)
Cultural identity may indirectly determine how a person within a particular cultural context takes action to prevent and treat a condition or a disease. Knowledge is one of predisposing factors that can influence both cultural identity and health behavior. Rural communities in Indonesia have their own cultural identity that may influence the health-related behavior of the residents. The Village of Duyung is one of example of this case. The lifestyle and medicine-related behavior of the residents might be influenced by the nature of its collective or communal culture. This report aims to present the level of awareness of the principles of healthy lifestyle and appropriate medicine-related behaviour in the Village of Duyung. A community empowerment program was designed and conducted in July and August 2023. All 23 participants were women with age ranged from. 26 to 47 years. The proportion of participants who were unaware of the principles of healthy lifestyles and medicine-related behavior was as high as 78.3 and 87.0%, respectively. There is a statistically significant difference in the final score of knowledge before and immediately after the training on the principles of healthy lifestyle and medicine-related behavior. The program demonstrated a significant change of the awareness and knowledge of some participants in the Village of Duyung on healthy lifestyle and the appropriateness of medicine-related behaviour. The impact on how this method of education contributes to cultural identity and consistent health-related behavior over longer time needs further study.